Our results-driven testing culture : - Lesch, Lyn (Rowman & Littlefield Education, 2007)
This book is intended to be a discussion point for how to develop a healthy relationship between personal experience and academic learning-which in light of our current results driven, testing culture, is the real benefit of the book